Psycho-social adaptation problems in mothers of children carrying Down Syndrome - Allyne Nóbrega Fortes; Marcos Venícios de Oliveira Lopes (Universidad de Alicante, 2012)
This descriptive study analyses possible psycho-social problems for mothers of children carrying Down Syndrome. It was carried out in a Treatment and Early Stimulating Unit in a Brazialian university. A structured outline of interviews was prepared for data collecting, and applied to a group of 13 women with children carrying D.S. regularly attending the unit. All behaviors were codified and grouped according to common adapting difficulties recorded by Callista Roy. Being the 'self-assessment' the commonest problem in all of them. Bio-psycho-social impairments were identified in those women not only for the D.S. diagnosis suffered from their children but for a certain fear to society pre-concept. The lack of knowledge and information about the illness as well as the paramount importance of an early stimulation and treatment contributed to magnify those adapting problems. The conclusion the study presented was there is a compensating adapting level of self-assessment in the analyzed women.